Specific cation effects on hemoglobin aggregation below and at physiological salt concentration - Medda, Luca (Langmuir : the ACS journal of surfaces and colloids, 2013)
Turbidity titrations are used to study the ion specific aggregation of hemoglobin (Hb) below and physiological salt concentration in the pH range 4.5-9.5. At a salt concentration 50 mM cations promote Hb aggregation according to the order Rb(+) > K(+) ~ Na(+) > Cs(+) > Li(+). The cation series changes if concentration is increased, becoming K(+) > Rb(+) > Na(+) > Li(+) > Cs(+) at 150 mM. We interpret the puzzling series by assuming that the kosmotropic Li(+) will bind to kosmotropic carboxylates groups-according to the law of matching water affinities (LMWA)-whereas the chaotropic Cs(+) will bind to uncharged protein patches due to its high polarizability. In fact, both mechanisms can be rationalized by invoking previously neglected ionic nonelectrostatic forces. This explains both adsorption to uncharged patches and the LMWA as a consequence of the simultaneous action of electrostatic and dispersion forces. The same interpretation applies to anions (with chaotropic anions binding to chaotropic amine groups). The implications extend beyond hemoglobin to other, still unexplained, ion specific effects in biological systems